The Comparative Analysis Of Learning Foreign Language Through Book And Learning Through Video Lessons - Oktamova, Moxigul; Ikromaliyeva, Gulsevar (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article presents a comparative analysis of the use of books and video textbooks in learning a foreign language. Both methods have their own advantages and disadvantages in the language learning process. The article analyzes the effectiveness of these two approaches and compares their role in the development of students' language skills.